The Transgenerational Transmission of the Paternal Type 2 Diabetes-Induced Subfertility Phenotype - Zatecka, Eva; Bohuslavova, Romana; Valaskova, Eliska; Margaryan, Hasmik; Elzeinova, Fatima; Kubatova, Alena; Hylmarova, Simona; Peknicova, Jana; Pavlinkova, Gabriela (Frontiers in Endocrinology, 2021)
Diabetes is a chronic metabolic disorder characterized by hyperglycemia and associated with many health complications due to the long-term damage and dysfunction of various organs. A consequential complication of diabetes in men is reproductive dysfunction, reduced fertility, and poor reproductive outcomes. However, the molecular mechanisms responsible for diabetic environment-induced sperm damage and overall decreased reproductive outcomes are not fully established. We evaluated the effects of type 2 diabetes exposure on the reproductive system and the reproductive outcomes of males and their male offspring, using a mouse model. We demonstrate that paternal exposure to type 2 diabetes mediates intergenerational and transgenerational effects on the reproductive health of the offspring, especially on sperm quality, and on metabolic characteristics. Given the transgenerational impairment of reproductive and metabolic parameters through two generations, these changes likely take the form of inherited epigenetic marks through the germline. Our results emphasize the importance of improving metabolic health not only in women of reproductive age, but also in potential fathers, in order to reduce the negative impacts of diabetes on subsequent generations.